If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2l + 2) = 24 Reorder the terms: 2(2 + 2l) = 24 (2 * 2 + 2l * 2) = 24 (4 + 4l) = 24 Solving 4 + 4l = 24 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4l = 24 + -4 Combine like terms: 4 + -4 = 0 0 + 4l = 24 + -4 4l = 24 + -4 Combine like terms: 24 + -4 = 20 4l = 20 Divide each side by '4'. l = 5 Simplifying l = 5
| 8x-32=5+10x | | -3(2t+9)=-57 | | (2y+2)*350=(0.6y+6)*350 | | 8x^3-30x^2+48=0 | | 2a+9=8a-9 | | 4(a-4)=16 | | 5(f-3)=-35 | | 10(s-3)=-58 | | 9x-3x=2x+20 | | 4x-(2x-8)=5(1+2x) | | 0.5x-7=3.9x-24 | | 7z-7=8 | | -3.6-6x=3.0 | | 18x-9-3x=36+3x | | x-1.2=2.2 | | 5t=5n+5v | | 7(3p+8)=2(p+9) | | 5x-10=6x+5 | | 1+2-51=8 | | 4y=300 | | (2x-7)+8x=(8x+28)+48 | | 16x+(30-x)26=18*30 | | 6x+9=-31-2x | | 8-3k=-4k+3 | | 27/-3=0 | | 66=2+8j | | 6x-18=3-12+4x | | 2+8x=-26+x | | 13x-4x-0= | | 6x+6=7x-14 | | 9m-27=45 | | 5h-7=3h-15 |